2011
DOI: 10.1002/pmic.201100085
|View full text |Cite
|
Sign up to set email alerts
|

Combined proteomic and transcriptomic analysis of the response of Bacillus anthracis to oxidative stress

Abstract: The endospore-forming Gram-positive pathogen Bacillus anthracis is responsible for the usually fatal disease, inhalational anthrax. The success of this pathogen is dependent on its ability to subvert elements of the innate immune system of its animal hosts. B. anthracis spores, which are the main infective agent, are engulfed and germinate in patrolling alveolar macrophages. In order for the infection to progress, the resulting vegetative cells must resist the antimicrobial oxidative burst mounted by the host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 68 publications
(94 reference statements)
3
45
0
Order By: Relevance
“…anthracis was cultured to log phase (OD 540 of ϳ0.3) prior to the addition of 800 M PQ, and time-dependent growth was monitored by measuring changes in optical density relative to that of untreated control cultures. This concentration was selected because our previous data showed that it perturbs but does not prevent growth of B. anthracis and because it was the condition that we previously used for a combined proteomic and transcriptomic study (30). The cultures treated with PQ showed a mild impairment of growth, consistent with previous data (30), and were unable to achieve the same stationary-phase density as that of untreated cultures (Fig.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…anthracis was cultured to log phase (OD 540 of ϳ0.3) prior to the addition of 800 M PQ, and time-dependent growth was monitored by measuring changes in optical density relative to that of untreated control cultures. This concentration was selected because our previous data showed that it perturbs but does not prevent growth of B. anthracis and because it was the condition that we previously used for a combined proteomic and transcriptomic study (30). The cultures treated with PQ showed a mild impairment of growth, consistent with previous data (30), and were unable to achieve the same stationary-phase density as that of untreated cultures (Fig.…”
Section: Resultssupporting
confidence: 74%
“…B. anthracis is predicted to experience significant oxidative stress within the phagolysosome of the host macrophage. Thus, we have been investigating the responses of B. anthracis to such stresses (30,41). Transcriptomic studies have shown the induction of a number of genes encoding putative iron import and siderophore biosynthetic systems during PQ treatment (28,30), which contrasts with the response of E. coli, which represses iron transport in favor of manganese import (3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…based on the available information about their survival mechanisms has yet to be undertaken (Christman et al, 1985;Inaoka et al, 1990;Farr and Kogoma, 1991;Givskov et al, 1994;Nitta et al, 2000;Sabra et al, 2002;Kabir et al, 2004;Passalacqua et al, 2006Passalacqua et al, , 2007Den Besten et al, 2009;Noor et al, 2009aNoor et al, , 2009bZuber, 2009;Pohl et al, 2011;Huillet et al, 2012;Murata et al, 2012;Den Besten et al, 2013;Nagamitsu et al, 2013). In relation to current studies on bacterial oxidative stress responses, the present study employed preliminary experiments to resolve the impact of increased concentration of the oxidant.…”
Section: Confirmative Demonstration Of E Coli and Pseudomonas Viabilmentioning
confidence: 99%